Information Status Predicts the Incidence of Gesture in Discourse: An Experimental Study. Issue 10 (26th November 2022) - Debreslioska, Sandra; Gullberg, Marianne
ABSTRACT: The study aimed to disentangle the influence of information status and referential form on the distribution of gestures in sustained discourse. Previous research shows that new and less accessible rather than old and more accessible information, expressed by rich rather than lean referential forms, is more likely to be accompanied by gestures. However, earlier studies have drawn on correlational results. This study probes the relationship between information status and gesture production experimentally. Participants retold stories referring to discourse entities as normal (Control), using only lexical noun phrases (NOUN condition), or only pronouns (PRONOUN condition). The results from the experimental conditions showed that speakers tend to produce gestures with reintroduced rather than maintained referents regardless of referential form. The findings suggest a strong and direct relationship between information status and gesture production when referential forms are controlled for, lending further support to a view of speech and gesture as an integrated system.